Study of the Spatial Effect of Geothermal on Surface Water Quality (Case Study of Ci Pamatutan Watershed, Parakansalak Sub-District) - Masykur, Fauzan Abdurrahman; Pras, Prasetiawan; Rianputra, M. Rafli Ariq; Umaya, Nesya Desfarivana; Gabriela, Vanesa Kelly; Tambunan, Mangapul Parlindungan; Supriatna, Supriatna (UI Scholars Hub, 2026)
Geothermal plays an important role in affecting surface water quality with both positive and negative effects. It becomes an efficient renewable energy source in generating electricity without producing harmful gases. However, the presence of geothermal affects the quality of surface water in a watershed. This research is focused on the Mount Salak geothermal area which has volcanic and tectonic activity. Parameters such as electrical conductivity (measured in millisiemens/cm) were used to measure the content of minerals and dissolved compounds in the water. Total Dissolved Solids (TDS) measured in ppt is used to quantify dissolved solids, while water acidity (pH) indicates the acidity or basicity of the water. There are three main locations of geothermal manifestations in the Ci Pamatutan Watershed, Parakansalak District, namely Anjing Crater (Ci Pamatutan Crater), Citaman Crater (Pulasari Taman Crater), and Hot Spring Pool (Ci Seupan). The spatial pattern of hot earth manifestation refers to the reservoir point below the earth's surface 300 meters from the fault and on observation above the earth's surface is marked by a basin pattern in each crater. Spatial patterns of surface water quality were observed with reference to river segmentation and the confluence of river orders from each spring. The research conclusion found that impact of surface water quality on the community occurs when there is a flash flood event, and clean water for the community is taken from the surface flow of the Perbakti slope sub-watershed, which is not affected by the presence of geothermal manifestations.